DAMPAK STIMULAN DANA PINJAMAN BERGULIR TERHADAP PERTUMBUHAN EKONOMI PADA PELAKU EKONOMI KREATIF (USAHA MIKRO KECIL DAN MENENGAH, UMKM) - Mansur, Muhammad; Junaidi, Junaidi; Machfudz, Masyhuri; Kamilah, Nahdhiyatul (Fakultas Ekonomi, UIN Maliki Malang, 2018)
The purpose of this study was to provide assistance to creative finance economic actors (MSMEs) and intervention of snacks production management by paying attention to halalan-thoyibah with all the attributes. The research method is participatory action research (PAR). The results of the study showed that (i) stimulant funds given to the target group took place 3 times. The application of the qordhu hasan model transaction formed appropriate technology named QH-9Kj, namely qordhu hasan on seven agreements : the number of group members, the number of loans, the number of returns, the number of groups, the amount of return time (for example per week), the amount of savings based on profit obtained, the amount of withdrawal of savings, the number of loans for the next round and the agreement on the amount of money filling voluntarily without being determined and (ii) the intervention of halal production and good by conducting counseling; the result is 89% satisfaction and carry out with a halal and thoyib production.